Optimizing Growth of Parkia speciosa Hassk Seedlings: The Synergistic Impact of Chicken Manure Briquette Dosage and Watering Intervals for Supporting Agroforestry Practices - Sri Hartini, Kansih; Dalimunthe, Afifuddin; Aini, Syarifah; Insani, Aqilah (Talenta Publisher, 2025)
Petai (Parkia speciosa Hassk) is a multi-purpose tree species (MPTS) that offers a sustainable solution for perennial cultivation in the Besitang District, within the Gunung Leuser National Park (GLNP) area, particularly in regions currently dominated by oil palm plantations. This study aims to obtain the dose of chicken manure briquettes and watering interval that produce the best growth of Petai seedlings. This study used a Factorial Completely Randomised Design (F-CRD) with observation parameters of height, diameter, number of leaves, shoot fresh weight, root fresh weight and shoot and root dry weight. The results showed that the interaction of manure briquette dose treatment and watering interval showed significant results on height, diameter, number of leaves, shoot fresh weight, shoot dry weight, and root dry weight but no significant effect found on the root fresh weight of Petai plants. The treatment 1 kg briquettes and watering every three days gave the best results in the parameters of height (15.57 cm), diameter increase (0.34 cm), number of leaves (103 strands), shoot fresh weight (39.96 grams), shoot dry weight (33.24 grams) and root dry weight (21.98 grams). Therefore, it is recommended to apply organic chicken manure briquette fertilizer at a dose of 1kg and watering frequency of once every three days for the preparation of Petai seedlings to planting in Besitang District